Characteristics of turbulent boundary layers over smooth surfaces with spanwise heterogeneities. (18th January 2018) - Medjnoun, T.; Vanderwel, C.; Ganapathisubramani, B.
Abstract : An experimental investigation of a turbulent boundary-layer flow over a heterogeneous surface is carried out to examine the mean flow and turbulence characteristics, and to document the variation of skin friction that might affect the applicability of traditional scaling and similarity laws. The heterogeneity is imposed along the spanwise direction and consists of streamwise-aligned smooth raised strips whose spanwise spacing S is comparable to the boundary-layer thickness ( S/[STIX]x1D6FF=O(1) ). Single-point velocity measurements alongside direct skin-friction measurements are used to examine the validity of Townsend's similarity hypothesis. The skin-friction coefficients reveal that the drag of the heterogeneous surface increased up to 35 % compared to a smooth wall, while velocity measurements reveal the existence of a log layer but with a zero-plane displacement and a roughness function that vary across the spanwise direction. Lack of collapse in the outer region of the mean velocity and variance profiles is attributed to the secondary flows induced by the heterogeneous surfaces. Additionally, the lack of similarity also extends to the spectra across all scales in the near-wall region with a gradual collapse at small wavelengths for increasing S . This suggests that the effect of surface heterogeneity is not necessarily felt at the smaller scales other than to reorganise their presence through turbulent transport.